‘At once pet, ornament, and “subject for dissection”’: The Unstable Status of Marine Animals in Victorian Aquaria - Silvia Granata (Cahiers Victoriens et Edouardiens)
Around the middle of the nineteenth century a new kind of domestic animal entered Victorian homes thanks to the invention of saltwater aquaria. Yet, marine species were very different from other, more usual pets: their marked otherness, and the limited contact allowed by the glass tank, made it more difficult to understand their behaviour, or to establish relations with them. Thus, numerous aquarium manuals were published: they offered guidance on the management of home tanks, but also instructed readers on how to fully appreciate and enjoy the new hobby; these texts thus provide a valuable source to understand the different ways in which early aquarists saw, conceptualised and related to sea animals. Indeed, I suggest that, due to the unfamiliar nature of most of these species, aquarium texts had a huge impact in shaping people’s perception of them, providing both conceptual frameworks and models for interaction. Through an investigation of the ways in which aquarium manuals represented tank residents and human relations with them, this article explores the unstable status of sea species in Victorian homes, discussing how, and why, they were simultaneously humanised and objectified, floating across the slippery boundaries between the categories of ornament, pet, scientific specimen, and food.